Determination of Lead (Pb) in stools of Lontra longicaudis (Olfers, 1818) by flame atomic absorption spectrometry (FAAS) - Cavallini, Nubya Gonçalves; Reis, Rorigo Arantes; Quadros, Juliana; Oliveira, Andrea; Nazário, Mariana Gallucci; Tiepolo, Liliani Marilia (Eclética Química, 2018)
The determination of metallic elements by flame atomic absorption spectrophotometry reaffirms the success of the technique for ecological and toxicological studies of environmental contamination. In order to contribute to the scientific research on anthropogenic contamination, the study of Lead in stools of Lontra longicaudis (Olfers, 1818) in the Guaraguaçu River Basin aims to understand the anthropogenic environmental contamination of the local ecosystem, located in one of the largest port areas in Brazil. Six samples were collected along the Guaraguaçu River. To determine the Lead concentration by the flame atomic absorption spectrophotometry method, samples were extracted with HNO3. Concentration values of approximately 1 mg L-1 were detected. There is a need to deepen the development of possible actions to control, monitor and inspection this element in the environment and in its main anthropogenic sources of contamination.